Falls in institutionalized elderly with and without cognitive decline A study of some factors - Baixinho,Cristina Lavareda (2019)
ABSTRACT. Falls in long-stay institutions for elderly people have a high prevalence, contributing to the physical and mental deterioration of institutionalized elderly. Objective: To determine the prevalence of falls among institutionalized elderly with and without cognitive decline, and to characterize the practices and behaviors of those with and without cognitive decline in managing fall risks, and relate them to some factors. Methods: The present correlational study was carried out with a sample of 204 institutionalized elderly, 50% of whom had cognitive decline. Results: The elderly with cognitive decline (40.2%) fell less often than those who did not have cognitive decline (42.2%) (p>0.05). Safety practices and behaviors were better in the elderly with cognitive decline (p<0.05). Most of the elderly with cognitive decline who fell took benzodiazepines (65.9%), in contrast with those without cognitive decline (32.2%). It was observed that 81.4% of the elderly without cognitive decline and 43.9% of those with cognitive decline who fell had a performance of over 12 seconds on the Timed Up and Go Test, where differences reached statistical significance in both groups of elderly. Conclusion: Data collected in the present study further the knowledge on risk factors in the genesis of falls and on the behavior of elderly with and without cognitive decline in maintaining their safety in self-care and accessibility.